Peningkatan Kemampuan Berpikir Kritis pada Pembelajaran Matematika melalui Model Problem Based Learning Siswa Kelas 4 SDN 1 Purwantoro Malang - Novitasari, Evi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to improve the critical thinking skills of grade IV students of SDN 1 Purwantoro Malang through the Problem Based Learning (PBL) learning model in Mathematics subjects. The study was conducted during the first semester of the 2023/2024 academic year involving 30 students. Data were collected through observation, tests, documentation, and interviews, and analyzed quantitatively and qualitatively. The results showed that the application of the PBL model was effective in improving students' critical thinking skills. It is evident from the increase in average critical thinking skills from 61.91 in the first cycle to 84.91 in the second cycle. Thus, the PBL model can make a significant contribution to Mathematics learning, making students more active, critical, and creative in solving problems.